Kickbacks in Medical Expert Markets - Stefan Felder (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2016)
This paper examines patient and overall welfare effects of kickbacks paid by a monopolistic hos-pital to competitive physicians in return for patient referrals. This practice is regarded as unethical and illegal in most cases. On the other hand, kickbacks can also enhance the distribution of labor in the production of medical services. In the context of medical services modelled as credence goods where patients need one of two possible treatments (minor or major), it is shown that pa-tient welfare is always lower with kickbacks than without. When the use of kickbacks is allowed, an equilibrium with overcharging (the patient requires the minor treatment but is charged for the expensive one) and one with overtreatment (the patient receives but does not require the major treatment) are possible. The latter results if patients can verify the treatment but not the diagno-sis, the former arises when no verifiability applies. Overall welfare is lowest in the equilibrium with overtreatment. Overcharging does not necessarily reduce overall welfare, as it depends on the degree of altruism among referring physicians. If they are solely extrinsically motivated, al-lowing kickbacks increases overall welfare. If physicians behave altruistically, a tradeoff arises between resource savings and guilt disutility from referrals. Additional equilibria emerge if the hospital can differentiate prices and post its own price for inexpensive treatments. Kickbacks continue to be predicted if physicians are not overly altruistic and no or only partial verifiability applies. In these cases, a prohibition of kickbacks improves the allocation. Kickbacks disappear, however, if treatment and diagnosis are verifiable, or if the hospital market is competitive.
Keywords: I11; I18; D80; 330